Evaluation of design parameters for deep-bed rapid sand filters - Hettiaratchi, Joseph Patrick Anthony; Nguyen, Cong Thanh; Lonani, B.N.; Watanabe, Y; CDG (Germany) (Bangkok : Asian Institute of Technology, 1981)
A process analysis method was developed for particle removal in deepened granular media filters, which would permit optimum filter design with a minimum of well designed pilot plant studies. Mathematical models purporting to describe the dependency of filter coefficient, on specific deposit a were examined, based on controlled filtration experiments. Using an experimental system of unisized medium grains with stabilized and destabilized suspensions, model parameters were evaluated for each sand size and filtration rate . Empirical relationships showing the dependency of model parameters on system variables were developed. Application of the proposed models in predicting the concentration and specific deposit profiles indicate that this method can permit prediction of filter performance, provided parametric dependence of model parameters is known.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Sewage -- Purification -- Rotating disc process